Avaliação de resposta imunológica aguda de camundongos c57bl/6 e balb/c frente à infecção por mycobacterium massiliense - SOUSA, Eduardo Martins de (2009)
Atypical mycobacteria are microorganism s appart from the etiological agents responsible for tuberculosis and leprosy. They are currently considered as emerging pathogens associated with simple surgical procedures, and are resistant to conventional antibiotics. The atypical mycobacterial infections is responsible for three in every 10 thousand people per year, but the incidence has been increasing as the number of individuals infected with HIV also increases. The low virulence of atypical mycobacteria associates its pathogenicity to decreased resistance of the host, and consequently it is necessary to better understand the interaction between host and microorganism. The cellular and humoral immune response of BALB/c mice and C57BL/6 mice infected with M. massiliense isolated from an outbreak of hospitals in the city of Goiania was evaluated. The isolate of M. massiliense used in this study was able to infect immunocompetent mice, which completely controlled the bacterial load before the 30 days of infection. The mechanisms by which these animals cleared the mycobacteria were: production of NO by peritoneal macrophages, presence of specific IgG1 and induction of mRNA for inflammatory cytokines, as well as regulatory cytokines in inflammation.